Fabrication of porous ZnO thin films via ammonium hydroxide: effects of etching time and oxidizer on surface morphology and surface roughness - S.S., Ng; P.K., Ooi; Yaakob, S.; Abdullah, M.J.; Abu Hassan, H.; Hassan, Z. (Universiti Kebangsaan Malaysia, 2014)
The effects of the etching time and oxidizer on the surface morphology and surface roughness of the porous zinc oxide (ZnO) thin films, which were formed using ammonium hydroxide (NH4OH) were investigated. The etching time was varied from 1  to 5 min. The oxidizer used was hydrogen peroxide (H2O2) solution. The ZnO thin films were obtained using radio- frequency magnetron sputtering on n-type silicon (111) substrate. The thickness of the ZnO thin films was approximately 1.34 μm. The morphology, topography and surface roughness of the porous ZnO were characterized using scanning electron microscope (SEM) and atomic force microscope. The SEM results showed that the surface morphology of the as-grown ZnO film has a leaf-like structure. However, this structure transformed into irregularly shaped pores upon exposure of the ZnO thin films to the etchant solutions. Increased etching time corresponded to increased pore size, which concurrently resulted in the formation of granular ZnO. Finally, it was found that the etching rate increases with the addition of H2O2 in the NH4OH solution.